Perbedaan edukasi spinal anestesi menggunakan video dan booklet terhadap tingkat kecemasan pasien pre anestesi spinal - Ubjaan, Natasya Putri; Burhan, Asmat; Dewi, Feti Kumala (Holistik Jurnal Kesehatan, 2025)
Background: Spinal anesthesia often causes anxiety in preoperative patients, which may affect the anesthesia process and postoperative recovery. Preanesthetic education is therefore needed to reduce patients’ anxiety levels. Purpose: To determine the difference in the effectiveness of spinal anesthesia education using video and booklet media on anxiety levels in pre–spinal anesthesia patients. Method: This study employed a quantitative approach with a quasi-experimental pre-test–post-test with control group design. A total of 38 participants were divided into a video group and a booklet group. Data were collected using the APAIS (Amsterdam Preoperative Anxiety and Information Scale) questionnaire. Data analysis was conducted using the Wilcoxon test and the Mann–Whitney U test. Results: There was a significant reduction in anxiety levels before and after the educational intervention in both the video and booklet groups (p < 0.05). Furthermore, a significant difference in anxiety levels was found between the two groups after the intervention, with a mean rank of 45.82 in the video group and 31.18 in the booklet group (p < 0.05). Conclusion: Preanesthetic education using both video and booklet media is effective in reducing patients’ anxiety levels. However, video-based education is more effective than booklet-based education in reducing anxiety among pre–spinal anesthesia patients.   Keywords: Anxiety; Booklet; Education; Preoperative; Spinal Anesthesia; Video.   Pendahuluan: Spinal anestesi sering menimbulkan kecemasan pada pasien preoperasi yang dapat berdampak pada proses anestesi dan pemulihan. Edukasi preanestesi diperlukan untuk menurunkan tingkat kecemasan tersebut. Tujuan: Untuk mengetahui perbedaan edukasi spinal anestesi menggunakan video dan booklet terhadap tingkat kecemasan pasien pre anestesi spinal. Metode: Penelitian kuantitatif dengan desain quasi experiment pre-test post-test with control group. Sampel berjumlah 38 partisipan yang dibagi menjadi kelompok video dan booklet. Instrumen menggunakan kuesioner APAIS. Analisis data menggunakan uji Wilcoxon dan Mann Whitney U. Hasil: Terdapat penurunan tingkat kecemasan yang signifikan sebelum dan sesudah pemberian edukasi baik pada kelompok video maupun booklet (p < 0.05). Selain itu, terdapat perbedaan tingkat kecemasan yang bermakna antara kedua kelompok setelah diberikan edukasi, dengan nilai mean rank kelompok video sebesar 45.82 dan kelompok booklet sebesar 31.18 (p < 0.05). Simpulan: Edukasi preanestesi spinal menggunakan media video dan booklet sama-sama efektif dalam menurunkan tingkat kecemasan pasien. Namun, edukasi menggunakan media video terbukti lebih efektif dibandingkan media booklet dalam menurunkan tingkat kecemasan pasien preanestesi spinal.   Kata Kunci : Booklet; Edukasi; Kecemasan; Pre Operasi; Spinal Anestesi; Video.